Keep It Simple: A Methodological Discussion of Wage Inequalities in the Spanish Hospitality Industry. - Sanchez-Cubo, Francisco; Mondéjar-Jiménez, José; García-Pozo, Alejandro; Maltagliati, Mauro (MDPI, 2023)
Human capital in hospitality has been widely addressed by applying sophisticated econometric methods. However, for the Spanish case, there was a gap in the analyses as the crucial importance of collective agreements was undervalued. This paper redesigns the conceptualisation of the variables and applies a subsequent new classification to job positions, as it deals with the outliers at different levels of rigorousness. Then, linearised and quantile regressions were run for each case, obtaining an outcome of thirty values for each variable. The analyses and comparisons show the high importance of collective agreements on salaries, the noticeable low values of human capital variables, and provides additional information for the nationality and gender gaps, the latter strikingly high in upper professional categories. Overall, this paper demonstrates the importance of a proper study design to prevent advanced econometric models from falling into bias and it minimises the differences between methods.
Keywords: Hostelería - Salarios - España; Recursos humanos; Hostelería - Gestión de personal - Modelos econométricos; Spain; Linearised regressions; Hospitality; Human capital; Quantile regressions